Growth dynamics in naturally progressing chronic lymphocytic leukaemia - Gruber, Michaela (Nature, 2019)
How the genomic features of a patient’s cancer relate to individual disease kinetics remains poorly understood. We leveraged the indolent growth dynamics of chronic lymphocytic leukaemia (CLL) to analyse growth rates and genomic patterns of leukaemia cells from 107 CLL patients, spanning decades-long disease courses. We found that CLL commonly demonstrates not only exponential expansion but also logistic growth, which is sigmoidal and reaches a certain steady state level. Each growth pattern was associated with marked differences in genetic composition, pace of disease progression and extent of clonal evolution. In a subset of patients, whose serial samples underwent next-generation sequencing, we found that dynamic changes in the CLL disease course were shaped by the genetic events that were already present in earliest indolent stages. Finally, by analysing growth rates of subclones compared to their parental clones, we quantified the growth advantage conferred by putative CLL drivers in vivo.